A Redox‐Induced Spin‐State Cascade in a Mixed‐Valent Fe3(μ3‐O) Triangle. (5th December 2016) - Govor, Evgen V.; Al‐Ameed, Karrar; Chakraborty, Indranil; Coste, Carla S.; Govor, Olena; Sanakis, Yiannis; McGrady, John E.; Raptis, Raphael G.
Abstract: One‐electron reduction of a pyrazolate‐bridged triangular Fe3 (μ3 ‐O) core induces a cascade wherein all three metal centers switch from high‐spin Fe 3+ to low‐spin Fe 2.66+ . This hypothesis is supported by spectroscopic data ( 1 H‐NMR, UV‐vis‐NIR, infra‐red, 57 Fe‐Mössbauer, EPR), X‐ray crystallographic characterization of the cluster in both oxidation states and also density functional theory. The reduction induces substantial contraction in all bond lengths around the metal centers, along with diagnostic shifts in the spectroscopic parameters. This is, to the best of our knowledge, the first example of a one‐electron redox event causing concerted change in multiple iron centers.